2017
DOI: 10.1177/1084822317703936
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk of Occupational Health and Safety Hazards for Home Healthcare Workers

Abstract: Given the increased prevalence of chronic disease and health care costs, more individuals are treated in the home, which has augmented the demand for more Home Healthcare Workers (HHCWs) in the field. HHCWs face multiple hazards with injury rates being more than double the national average; however, current studies on HHCWs have provided limited understanding of their occupational safety & health experiences and exposures. The aim of this study was to assess the frequency and risk of exposures through percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…In the United States, nearly 90% of home health care workers are women. 4 This was reflected among the studies identified: 13 reported on the gender makeup of their samples, ranging from 86% females 27 to 95% females. 15,22,30,31 Two studies surveyed only women health care workers’ experiences.…”
Section: Resultsmentioning
confidence: 98%
“…In the United States, nearly 90% of home health care workers are women. 4 This was reflected among the studies identified: 13 reported on the gender makeup of their samples, ranging from 86% females 27 to 95% females. 15,22,30,31 Two studies surveyed only women health care workers’ experiences.…”
Section: Resultsmentioning
confidence: 98%
“…We used a bibliometric Science Mapping tool to visualize the international collaboration network and found that the top ten countries with the largest number of publications (Figure 3.) include America (83), Canada (42), Brazil (39), England (30), France (12), Spain (11), the Netherlands (11), South Africa and China (11), accounting for 67.16% of the total publications. Combined with Table 1, it can be found that Americas accounted for 60.74%, and Europe accounted for 31.11% of the total outputs in the top ten countries and also played vital roles in establishing links with other countries.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Research on HHCWs should receive more attention. In view of the aging of the population, the increasing cost of chronic diseases and health care, more people need to be treated at home, which increases the demand for more HHCWs [30]. HHCWs may also be injured by musculoskeletal disorders [90], stress [33], exposure [91], etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations